Perjuangan Rakyat Surakarta Dalam Revolusi Kemerdekaan 1946-1949 - Farichatul Izza, Dewi Naila (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2023)
This article discusses the situation during the Indonesian War of Independence in Surakarta, particularly in relation to the political and social circumstances in Indonesia at that time. In 1945, Indonesia declared its independence after more than three and a half centuries of Dutch colonial rule. However, the Netherlands did not recognize Indonesia's independence and initiated military operations to reclaim its former colony. When the Dutch began their military operations, Surakarta became one of their primary targets. Surakarta was an important city in Central Java, serving as a center of government and culture in the region. Additionally, Surakarta was strategically significant due to its access to a seaport and major transportation routes in Central Java. At that time, Surakarta also had a relatively strong military presence compared to other areas in Central Java. This made the Dutch view Surakarta as a strategic point that needed to be controlled in order to regain their colony. However, the people of Surakarta did not remain passive and prepared themselves to resist the Dutch invaders. The people of Surakarta were fueled by a strong sense of nationalism and saw the struggle for independence as a duty. Thus, the background of the War of Independence in Surakarta is rooted in the political and social situation in Indonesia at the time, where Indonesians were fighting for their independence while the Dutch conducted military operations to reclaim their former colony, including Surakarta, which had a relatively strong military presence..